Strategi pengelolaan sampah kota terintegrasi menuju zero waste - Sutisna, Muhammad Aziz Rizal (Institute for Advanced Science, Social, and Sustainable Future, 2024)
The Sustainable Development Goals (SDGs), declared by 193 countries at the UN on September 25, 2015, serve as the foundation for global development. Building upon previous agendas, the SDGs emphasize three pillars of sustainable development: social, economic, and environmental. Cities, as centers of economic growth, face complex challenges in waste management. Urban waste, especially organic waste, requires special handling as it tends to decompose and create adverse environmental impacts if not managed properly. In the context of Indonesia, more than 65% of urban waste is organic, primarily food leftovers. To mitigate its impact, waste management is not sufficient merely with collection, transportation, and disposal at final disposal sites (TPA). Waste must be processed into useful goods, such as through recycling. This research proposes a Zero Waste approach to urban waste management. This concept involves waste prevention from the outset, reduction, reuse, recycling, and minimal waste residual management. Many cities worldwide, such as Canberra, Adelaide, and Stockholm, have successfully implemented Zero Waste strategies. In the Indonesian context, Surabaya is a successful example of effective urban waste management, involving various programs from waste banks to electricity generation from landfill gas. However, challenges in urban waste management persist. There is a need for new initiatives, such as involving more stakeholders from private to public sectors in the Zero Waste concept, and strengthening the government's role in implementing regulations supporting sustainable waste management. Additionally, education and public campaigns are crucial to raise awareness among the public about the importance of responsible waste management. Thus, this research highlights the importance of Zero Waste strategies in addressing urban waste management issues to achieve sustainable development goals.